THE EFFECT OF INTERRUPTIONS IN CONSUMPTION ON THE PROCESS OF EMOTIONAL AND COGNITIVE ADAPTATION TO HEDONIC EXPERIENCES: A STUDY OF CONSUMER DYNAMICS - Zaenal Aripin; Arif Budi Raharja; Ngurah Made Novianha Pynatih (PT. Kreatif Indonesia Satu, 2024)
This research explores the influence of interruptions in consumption on the emotional and cognitive adaptation process and consumers' hedonic experiences. By involving 1300 respondents, this research analyzes various types of interruptions that may occur during the consumption experience, explores the emotional responses that arise, and identifies the level of emotional adaptation that occurs. Next, product or service characteristics, consumption situation, and timing of consumption experience are explored as contextual factors that moderate consumers' cognitive adaptation to interruptions. Results suggest that technological interruptions tend to decrease levels of emotional adaptation, while social interactions may increase them. In addition, product complexity requires a higher level of cognitive adaptation, especially in formal consumption situations. These factors were also found to moderate consumers' hedonic experiences, with matching product expectations and intuitiveness enhancing positive experiences. The conclusion states that marketing strategies and business management need to consider not only the types of interruptions that may occur but also contextual factors involving product or service characteristics and consumption situations to increase consumer satisfaction.